Different Extraction Approaches for the Analysis of Melatonin from Cabernet Sauvignon and Feteasca Neagra Wines Using a Validated HPLC-FL Method - Sandra A. V. Eremia; Camelia Albu; Gabriel L. Radu; Marian Ion (Molecules, 2023)
In recent years, the wine industry has shown a considerable degree of interest in the occurrence of melatonin in wines. Sample pretreatment may be the most important step in trace analysis. Since wine is a complex matrix and melatonin is present in low amounts (ppb), an adequate extraction technique is required. In this study, the effect of several extraction methods, such as solid phase extraction (SPE), Quick, Easy, Cheap, Effective, Rugged, and Safe extraction (QuEChERS), and dispersive liquid–liquid micro-extraction (DLLME) was studied and the variable parameters that can arise throughout the extraction process were optimized to obtain the best results. A high-performance liquid chromatography with fluorescence detector (HPLC-FL) method was adapted and validated, including measurement uncertainty, for the analysis of melatonin in wines and to assess the efficiency of the extraction yield. After comparing the acquired results, the DLLME method was optimized. Extraction recoveries values ranging from 95 to 104% demonstrated that the approach may be successfully applied for the extraction and concentration (enrichment factor of almost eight) of melatonin in wine samples prior to HPLC-FL analysis. The first report of melatonin levels in Feteasca Neagra wines has been made. The data obtained for Cabernet Sauvignon revealed that the final levels of melatonin in the wines are dependent on the winemaking process.